2009
DOI: 10.1097/fjc.0b013e31819fd4e7
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Prevents Myocardial Reperfusion Injury by Activating the Adenosine Receptor

Abstract: Metformin improves cardiovascular outcomes in patients with type 2 diabetes compared with other glucose-lowering drugs. Experimental studies have shown that metformin can increase the intracellular concentration of adenosine monophosphate, which is a major determinant of the intracellular formation of adenosine. We hypothesize that metformin, given at reperfusion, can limit myocardial infarct size due to increased adenosine receptor stimulation. Isolated perfused hearts from Sprague-Dawley rats were subjected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 32 publications
2
64
0
Order By: Relevance
“…Metformin has beneficial effects on ischemic heart decreasing cardiac risk factors and improving clinical outcomes in human as well as recovering left ventricular functions in experimental animals [26][27][28]. However, the mechanisms by which metformin exerts these cardioprotective effects remain unclear.…”
Section: Discussionmentioning
confidence: 96%
“…Metformin has beneficial effects on ischemic heart decreasing cardiac risk factors and improving clinical outcomes in human as well as recovering left ventricular functions in experimental animals [26][27][28]. However, the mechanisms by which metformin exerts these cardioprotective effects remain unclear.…”
Section: Discussionmentioning
confidence: 96%
“…In a working-heart perfusion model where metformin is administered before a mild ischemic episode, the antidiabetic drug improved rat cardiac functional postischemic recovery (Legtenberg et al, 2002). It has been also shown that metformin given at the time of reperfusion reduced myocardial infarct size in both nondiabetic and diabetic hearts (Bhamra et al, 2008;Paiva et al, 2009). In these two last studies, the protective action of metformin was associated with a PI3K-mediated inhibition of the mitochondrial permeability transition pore opening and with increased intracellular formation of adenosine.…”
Section: Metformin In Myocardial Injurymentioning
confidence: 97%
“…In addition, adenosine produced during cardiac ischaemia [144] and drugs interacting with the adenosine receptor, such as metformin [145], are able to block mitogenic effects and MAPK activity downstream of IGF-1, rather promoting the PI3K pathway and its favourable antiischaemic and anti-atherogenic effects.…”
Section: From Risk Factors To Atherothrombosis Through Low Igf-1-medimentioning
confidence: 99%